La familia y el aprendizaje de los estudiantes con necesidades educativas especiales - Tuabanda Guilcarema, Daniel Santiago (2021)
This research about the family and the learning process of students with educational needs emphasizes the impact that the family has on educational aspects as a guide and guide in the learning that takes place at home. The first chapter describes the existing problem due to the lack of participation of the family in the learning process, emphasizing that family’s support is such a necessary tool in learning, its contribution facilitates a better performance of the student within the school problem and also the research objectives are stated..........